Ecological studies on the nepenthes species along Kaingaran Trail of Mount Trus Madi, Sabah, Malaysia - Alviana Damit (2019)
This study aimed to provide an insight into the current status of the Nepenthes community on Mount Trus Madi and the implications to their conservation. Ten 0.01 ha Nepenthes plots were established along the Kaingaran summit trail. A total of five Nepenthes taxa were identified, namely the Nepenthes tentaculata, N. zakriana, N. macrophylla, N. lowii and natural hybrid N. x trusmadiensis. The most abundant species was N. tentaculata with number of individuals was more than 75% from the total number of individuals of all species. In contrast, the other four taxa have a smaller distribution and less abundant along the Kaingaran trail. All species have significantly aggregated population dispersion pattern indicating that they grow in grouped and tend to survive best in particular favourable patches. Population structure of N. tentaculata showed higher number of seedlings compared to juveniles and mature individuals, indicating that its population is healthy, stable and growing. Meanwhile, the N. lowii, N macrophylla and N. x trusmadiensis showed lower number of seedlings and juveniles that may suggesting the inability of their seeds to germinate or the seedlings and saplings to survive and grow, that may lead to uncertain regeneration. By using Generalized Estimating Equation (GEE) approach, it was found that there was a significant reduction of the abundance of N. macrophylla between year 2016 and 2017, suggesting it was potentially at risk of population declined. Trail impact assessment was conducted using the Generalized Linear Models (GLM) to assess the effects of the trail on the abundance and mortality of the Nepenthes plants at different distances from the trail. The abundances of Nepenthes were significantly higher along the trail than further away while their mortalities were significantly highest at the zones that furthest from the trail. Their seedling individuals that were located at furthest from the trail, were also more likely to die compared to their seedlings adjacent to the trail. Evidently, the Nepenthes plants in this study were preferred to grow and survived the best along the trail, where the forest gap was wider, light intensity was higher and less competition with other plants, compared to the area furthest from the trail. Correlation analysis Spearman rank correlation coefficients was used to identify the relationship between the density of Nepenthes and the changes in stand structures and other factors along the elevation profile. The density of N. lowii was significantly correlated to the vegetation type and mean tree height where they were only grow well on summit scrub vegetation which have shorter trees. Meanwhile, the density of N. macrophylla was significantly correlated with the total tree basal area and altitude where they were restricted to elevation above 2,500 m and was more abundant on vegetation with lower tree basal areas. These indicate that both N. lowii and N. macrophylla species displayed a very narrow habitat specificity compare to the other Nepenthes species. The data and findings from this study are valuable as baseline data for future study comparison and thereafter will enable further effective conservation management and monitoring plans on Nepenthes community in Mount Trus Madi.